Labeo rohita Mx1 exhibits the critical structural motifs of the family of large GTPases of mammals and is activated by rhabdovirus vaccination and bacterial RNA stimulations. Issue 1 (1st February 2022) - Samanta, Mrinal; Satapathy, Sweta; Paichha, Mahismita; Choudhary, Pushpa
Abstract: Myxovirus resistance (Mx) proteins belonging to the dynamin superfamily of high molecular weight GTPases exist in various isoforms and play crucial role in innate immunity. In addition to the isoforms, Mx1 also plays important role in exerting its anti-viral actions against a broad range of animal RNA viruses. In rohu ( Labeo rohita), mx 1 full-length cDNA sequence consists of 2440 nucleotides (nt) encoding 628 amino acids (aa) polypeptide of 71.289 kDa. Structurally, it belongs to the family of large GTPases with one DYNc domain (13-257aa) comprising of dynamin family motifs (LPRGSGIVTR) and the tripartite GTP-binding motifs (GDQSSGKS, DLPG and TKPD) at the N-terminal and one GED domain (537-628aa) at C-terminus. Rohu Mx1 is closely related to zebrafish Mx1 and is widely expressed in gill, liver, kidney, spleen and blood. In response to rhabdovirus vaccinations, poly I:C stimulation and bacterial infections, mx 1 gene expression in rohu was significantly ( p < 0.05) induced in majority of the tested organs/tissues. Stimulation of rohu gill cell line with bacterial RNA also induced mx 1 gene expression. Together these data suggest the important role of Mx1 in innate immunity in rohu against wide spectrum of fish pathogens.